MAKING NA AND PDA MEDIUM AS MICROORGANISM GROWTH MEDIA - Musdalifa (LP2M Universitas Bina Mandiri Gorontalo, 2023)
Microorganisms can be grown and developed on a substrate called medium. With the medium of growth, microbia activity can be studied and with the growing medium can be done isolation of microbes with pure culture, propagation, testing of physiological properties, and calculation of the number of microbes. This study aims to find out how to make growth media NA bacteria and PDAs. The method used in this study is an experimental method conducted at the Microbiology Labolatorium of Bina Mandiri University gorontalo. The results showed that the creation of na and PDA bacterial growth media was successfully carried out. Medium function (NA) based on the chemical composition is a non-synthetic or semi-scientific medium, based on consistently a solid medium, to grow bacteria e.g. in meat, (PDA) including solid media, based on the chemical arrangement including synthetic to grow fungi for example in potatoes.